2012
DOI: 10.5551/jat.12856
|View full text |Cite
|
Sign up to set email alerts
|

Value and Level of Galectin-3 in Acute Myocardial Infarction Patients Undergoing Primary Percutaneous Coronary Intervention

Abstract: Aim: This study investigated the impact of the circulating galectin-3 level on the 30-day prognostic outcome in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI).Results: The galectin-3 level was determined using ELISA. Our results demonstrated that the circulating level of galectin-3 was significantly higher in STEMI patients than in healthy control subjects (p<0.001). As compared with patients with galectin-3 <7.67 ng/mL, patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 36 publications
6
74
3
3
Order By: Relevance
“…As described above, Tsai et al showed that circulating Gal-3 is a strong independent predictor of the combined 30-day MACO, defined as advanced congestive heart failure (CHF) and 30-day mortality (p < 0.0001), in STEMI patients undergoing pPCI [33]. Lisowska et al reported Gal-3 to predict mortality in mid-term follow-up of patients after AMI [8].…”
Section: Gal-3 and Prognosismentioning
confidence: 92%
See 4 more Smart Citations
“…As described above, Tsai et al showed that circulating Gal-3 is a strong independent predictor of the combined 30-day MACO, defined as advanced congestive heart failure (CHF) and 30-day mortality (p < 0.0001), in STEMI patients undergoing pPCI [33]. Lisowska et al reported Gal-3 to predict mortality in mid-term follow-up of patients after AMI [8].…”
Section: Gal-3 and Prognosismentioning
confidence: 92%
“…Firstly, the most common finding among such investigations is that circulating Gal-3 levels are elevated in ACS/AMI, being released during the acute phase of AMI [31,[33][34][35][36][37][38][39]. Indeed, Gal-3 could be part of a survival mechanism of the injured myocardium to cope with the ischemic insult [14].…”
Section: Gal 3 In Acsmentioning
confidence: 99%
See 3 more Smart Citations